Commercial Hinterland of Gorkha Bazaar - Dhakal, Keshav Raj (The Third Pole: Journal of Geography Education, 2014)
Present study attempts to trace out the characteristics of Gorkha Bazaar and its commercial hinterland on the basis of flow of goods and commodities. The study is based on primary data collected through a field survey. Altogether 135 functional units (about 30 percent of the total) were sampled for data collection. Gorkha Bazaar, being the head quarters of Gorkha district is an administrative center as well as a commercial market center of peripheral villages. The commercial function dominates all other functions. Three of the most important functions are grocery store, catering and fancy and cloths store. The wholesaling and personal services are relatively low in the market. The hinterland of Gorkha bazaar is limited strictly within the boundary of the district. DOI: http://dx.doi.org/10.3126/ttp.v11i0.11524 The Third Pole Vol. 11-12, 2012 page:12-15